Jurnal Teknologi Dirgantara Periode 2016-2020: Sebuah Analisis Bibliometrika - Rochani Rahayu; Sulisnaeni (Jurnal Gema Pustakawan, 2021)
Bibliomteric analysis was carried out on the Aerospace Technology Journal for the 2016-2020 period with the aim of knowing: 1) The number of articles published; 2) authorship patterns; 3) Degree of collaboration; 4) The gender of the author; 5) The most productive writer; 6) The institution where the author works; 7) The city where the author works and 8) The most research topics. The data source used is the Aerospace Technology Journal which is accessed from http://jurnal.lapan.go.id/index.php/jurnal_tekgan. The data recorded were the title and number of articles, names and number of authors, agencies and cities where the authors worked. The results of the analysis showed that 80 article titles were published, written by 114 people, with the composition of men (93 people; 81.58%) and women (21 people; 18.42%). There were 32 articles written individually (40%) and 48 articles written collaboratively (60%), with a degree of collaboration value of 0.60. Heru Budi Wibowo and Kendra Hartaya are writers from LAPAN and they contributed the most, namely writing 5 articles each. ITB and LAPAN are the institutions that contribute the most in writing articles. It is known that 2 universities from abroad also disseminated their research results in the journal, namely Universität München and the University of Rome. It is noted that Rumpin Tangerang is the city where most writers work. Most research topics are about rockets. The conclusion of the study is that from published articles, it is noted that male authors are more dominant, more articles are written in collaboration, with the largest number of institutions being LAPAN and ITB. The Journal of Aerospace Technology is known overseas